2015
DOI: 10.5539/hes.v6n1p24
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Writing Anxiety and Self-Efficacy among EFL Graduate Students in Taiwan

Abstract: This study investigates research writing anxiety and self-efficacy beliefs among English-as-a-Foreign-Language (EFL) graduate students in engineering-related fields. The relationship between the two writing affective constructs was examined and students' perspectives on research writing anxiety were also explored. A total of 218 survey responses from engineering graduate students at Taiwanese universities were analyzed, along with qualitative data from open-ended questions and semi-structured interviews. The f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
60
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(71 citation statements)
references
References 30 publications
10
60
0
1
Order By: Relevance
“…The confidence in self-regulatory strategies, the self-regulation of cognitive development, the long-term and intermediate-term goal setting, and the determination in spite of difficulties are characteristics shared by self-believers, which suggest that self-efficacy is an emotional construct closely related with metacognition (Jones 2008;Williams and Takaku 2011). Concerning writing selfefficacy, the literature reports a positive correlation between such factor and a positive writing performance (Pajares and Valiante 2006;Jones 2008;Prat-Sala and Redford 2012;Stewart et al 2015;Ho 2016). In fact, recent research has found that writing self-efficacy is a more significant predictor of a good writing performance than writing anxiety itself (Woodrow 2011;Sander-Reio et al 2014).…”
Section: Writing Self-efficacymentioning
confidence: 99%
See 3 more Smart Citations
“…The confidence in self-regulatory strategies, the self-regulation of cognitive development, the long-term and intermediate-term goal setting, and the determination in spite of difficulties are characteristics shared by self-believers, which suggest that self-efficacy is an emotional construct closely related with metacognition (Jones 2008;Williams and Takaku 2011). Concerning writing selfefficacy, the literature reports a positive correlation between such factor and a positive writing performance (Pajares and Valiante 2006;Jones 2008;Prat-Sala and Redford 2012;Stewart et al 2015;Ho 2016). In fact, recent research has found that writing self-efficacy is a more significant predictor of a good writing performance than writing anxiety itself (Woodrow 2011;Sander-Reio et al 2014).…”
Section: Writing Self-efficacymentioning
confidence: 99%
“…al. 2014;Ho 2016). Nevertheless, to the best of my knowledge, very little research has been done concerning writing anxiety in secondary school EFL students.…”
Section: Writing Anxietymentioning
confidence: 99%
See 2 more Smart Citations
“…Most studies agree with that the learning apprehensions cause students feel frustrating and becoming weaker in learning process. (Krashen, 2016, Tomlinson, 1981) Students tend to feel be demotivated in writing can hold negative attitude toward their writing tasks, producing papers of low quality, have negative impressions of their own writing and are more likely to avoid situations where writing is required (Ho, 2016;Sanders-Reio, et al, 2014). Hence, promoting learners' affirmative attitudes for learning has become a fundamental key to an effective and successful writing course.…”
Section: Introductionmentioning
confidence: 99%